RIGHTS AND OBLIGATIONS OF THE GUARDIANS TO THE INHERITANCE OF MENTAL DISABLED CHILDREN - Fitriyati, Yusida; Zuhdi, Muhammad (Nurani, 2020)
The law protects the interests of individuals under all circumstances, including children with mental disabilities in term of incapacity due to legal incompetence. Law Number 8 of 2016 concerning Persons with Disabilities. Article 5 states that the Unitary State of the Republic of Indonesia guarantees the survival of every citizen, including persons with disabilities, in this case persons with disabilities who are Muslims have a legal position and have the same human rights as Indonesian citizens and as an inseparable part of the Indonesian citizens and society. is a mandate and a gift from God Almighty, to live progressively and develop fairly and with dignity including obtaining justice and legal protection. Therefore, as a legal subject, people with mental disabilities are represented by their guardians in all their life activities. It is included in the control of the use of inheritance that is obtained. For this reason, this paper is made with a focus on the study of how the rights and obligations of guardians to the inheritance of mentally disabled children in Indonesia and global cultural relativism?